(untitled) (Research, Society and Development, 2025)
Transmissible Venereal Tumor (TVT) is a contagious neoplasm of high clinical relevance in dogs, mainly affecting stray animals. Being a contagious neoplasm, during intercourse, the clinical signs observed include: vulvar masses or nodules, serosanguineous discharge (hemorrhage), excessive licking of the genital area, local swelling, and, in advanced cases or with metastasis, apathy, weight loss, or urinary/intestinal obstruction may occur. This study aims to report the case of a stray female dog rescued in Rolim de Moura – RO, describing the clinical manifestations, diagnosis, therapeutic approach, and treatment evolution. The study is based on information recorded in the medical records provided by the clinic responsible for the patient’s follow-up. It is expected to provide detailed data on the presentation of TVT, the effectiveness of the treatment, and important aspects of clinical monitoring, contributing to regional knowledge and to raising awareness about the prevention and proper management of transmissible diseases in stray dogs.